Chromosomal Distribution of Endogenous Jaagsiekte Sheep Retrovirus Proviral Sequences in the Sheep Genome - Carlson, Jonathan (American Society for Microbiology, 2003)
A family of endogenous retroviruses (enJSRV) closely related to Jaagsiekte sheep retrovirus (JSRV) is ubiquitous in domestic and wild sheep and goats. Southern blot hybridization studies indicate that there is little active replication or movement of the enJSRV proviruses in these species. Two approaches were used to investigate the distribution of proviral loci in the sheep genome. Fluorescence in situ hybridization (FISH) to metaphase chromosome spreads using viral DNA probes was used to detect loci on chromosomes. Hybridization signals were reproducibly detected on seven sheep chromosomes and eight goat chromosomes in seven cell lines. In addition, a panel of 30 sheep-hamster hybrid cell lines, each of which carries one or more sheep chromosomes and which collectively contain the whole sheep genome, was examined for enJSRV sequences. DNA from each of the lines was used as a template for PCR with JSRV gag-specific primers. A PCR product was amplified from 27 of the hybrid lines, indicating that JSRV gag sequences are found on at least 15 of the 28 sheep chromosomes, including those identified by FISH. Thus, enJSRV proviruses are essentially randomly distributed among the chromosomes of sheep and goats. FISH and/or Southern blot hybridization on DNA from several of the sheep-hamster hybrid cell lines suggests that loci containing multiple copies of enJSRV are present on chromosomes 6 and 9. The origin and functional significance of these arrays is not known.